Me being me is exactly as insane as you being you - Hasak-Lowy, Todd 1969- (Simon Pulse, 2015)
Through a series of lists, a narrator reveals how fifteen-year old Darren's world was rocked by his parents' divorce just as his brother, Nate, was leaving for college, and a year later when his father comes out as gay, then how he begins to deal with it all after a stolen weekend with Nate and his crush, Zoey